2020
DOI: 10.1097/brs.0000000000003687
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Relationship Between Bony Fusion After Anterior Cervical Discectomy and Fusion and Heterotopic Ossification After Cervical Disc Arthroplasty in Hybrid Surgery?

Abstract: Study Design. Retrospective analysis. Objective. The aim of this study was to investigate the relationship between bony fusion after anterior cervical discectomy and fusion (ACDF) and heterotopic ossification (HO) after cervical disc arthroplasty (CDA) in hybrid surgery (HS). Summary of Background Data. The mechanism of postoperative bone formation still remains unknown. It is considered a risk factor in CDA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…The biomechanical changes of adjacent intervertebral disc, facet joint, and stress on the instrumentation during fusion process through longitudinal study paradigm has been poorly reported. In the present study, the cervical spine-implant FE models were developed based on the CT information of a patient who underwent single-level ACDF at pre-operation, immediately post-operation, and 3 and 6 months after surgery, representing non-fusion, incomplete fusion, and complete fusion stages, respectively ( Noordhoek et al, 2019 ; He et al, 2020 ; Abudouaini et al, 2021 ). To the best of our knowledge, this is the first study to simulate the biomechanical environment at different fusion stages after ACDF based on the patient’s follow-up data.…”
Section: Introductionmentioning
confidence: 99%
“…The biomechanical changes of adjacent intervertebral disc, facet joint, and stress on the instrumentation during fusion process through longitudinal study paradigm has been poorly reported. In the present study, the cervical spine-implant FE models were developed based on the CT information of a patient who underwent single-level ACDF at pre-operation, immediately post-operation, and 3 and 6 months after surgery, representing non-fusion, incomplete fusion, and complete fusion stages, respectively ( Noordhoek et al, 2019 ; He et al, 2020 ; Abudouaini et al, 2021 ). To the best of our knowledge, this is the first study to simulate the biomechanical environment at different fusion stages after ACDF based on the patient’s follow-up data.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study also found a significant relationship between bony fusion and HO occurrence in patients who underwent HS including TDR and ACDF. 20 We postulate that, in the context of the bone formation process, HO may be a reflection of individual osteogenic capacity and patients with more remarkable osteogenic ability have a higher incidence of HO postoperatively. Our findings showed that preoperative ossification was a potential risk factor for HO, and patients with preoperative ossification were nearly 3 times more likely to develop HO than those without preoperative ossification.…”
Section: Discussionmentioning
confidence: 99%
“…The disease results in disability and, if not treated, in the development of chronic discirculatory encephalopathy, cervical myelopathy, or ischemic stroke, and significant disability of the patients. In foreign practice, the relationship between a degree of cerebral neurological insufficiency and vascular lesions at various clinical and morphological stages of cervical osteochondrosis has been confirmed [2]. At the initial stages of the disease, vertebrobasilar circulatory disorders are a consequence of sympathetic (reflex) or compressive-irritative (compressionreflex) processes in the vertebral arteries.…”
Section: Introductionmentioning
confidence: 94%
“…The second stage of the disease is a consequence of the progression of histochemical and pathomorphological processes of the first stage. The loss of fixation properties by Our Experience in the Treatment of Vertebrobasilar Insufficiency Due to Cervical Spine Disorders Beslan S. Dzhilkashiev 1,2 *, Gennadiy I. Antonov 1,2 , Gennadiy E. Chmutin 1 , Keith Simfukwe 1 , Edward R. Miklashevich 2 , the annulus fibrosus results in the instability of the spinal motor segment [3], resulting in dynamic narrowing of the spinal canal, irritation, and compression of the vertebral arteries.…”
Section: Introductionmentioning
confidence: 99%